UPAYA MENGIMPLEMENTASI WIBAWA PENEGAK HUKUM MELALUI PENEMUAN HUKUM - Soumena, M. Yasin (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
The existence of laws in the midst of society is to protect the interests of human beings that need to be enforced and implemented. In enforcement, often clash between fair and unfair, but all that is relative. Therefore, to fulfill a sense of justice, any rule of law made always comes with an explanation. However, once it was called the explanation, it often creates a new explanation for just described